Initiatives on the metropolitan border of Buenos Aires: 1920-2020 - López Goyburu, Patricia Lucia (2024)
The metropolitan border of Buenos Aires has been conceived in different ways between 1920 and 2020. The tensions between the existing city and the proposed city invite us to reflect on how urban documents shape different initiatives to define the metropolitan border. We hold the hypothesis that the initiatives that define urban plans and regulations respond to different problems. To do this, we focus on the critical review of 4 urban planning initiatives that affect the metropolitan edge: "segmenting growth"; "contain growth"; "know the territory" and "decentralize growth". The initiatives by urban planning documents show that in some moments the metropolitan border is conceived as a border while in others it is conceived as a space to be explored and known or also as a place to receive urban growth. The results reflect that the way of thinking about the metropolitan border is being built through different episodes that confirm the concerns and interests about them.